Failure analysis in aluminium turbocharger wheels. (March 2016) - Moreira, M.F.
Abstract: This paper presents a failure analysis conducted in aluminium compressor wheels used in diesel turbocharged engines. These wheels were made with machined AA 2618T652 alloy and installed in light truck engines, which were used in rural and industrial atmospheres. The premature failures of the wheels happened after life between 40, 000 km and 300, 000 km, while the expected life was about 1, 000, 000 km. The present investigation showed that a fatigue process was triggered by intergranular corrosion on the upper camber surface of the wheel. A set of immersion corrosion tests was carried out to evaluate intergranular corrosion susceptibility of the alloy. The root-cause for the formation of the intergranular corrosion cracking in the compressor wheels could not be identified in the present investigation. The overall results indicated that an "in service" contamination of the compressor surface started the intergranular corrosion cracking, promoting the fatigue failure of the wheels. Highlights: Premature failures of turbocharger aluminum compressor wheels were caused by fatigue. Fatigue was triggered by intergranular corrosion on the upper camber surface. A set of corrosion immersion confirmed that the microstructure was susceptible to intergranular corrosion. The root-cause for intergranular corrosion cracking in the wheels could not be identified in the present investigation.